Retrospective analysis of glomerular filtration rate estimated using different equations with and without adjustment to individual body surface area - Sara Armani; Julia Stingl; Thomas Forst; Josef Höfler; Hannah Wecker; Astrid Trion (Medicine in Drug Discovery)
The assessment of the influence of renal function on the pharmacokinetics of a new drug is pivotal in many clinical development programs. In clinical trials, renal function is commonly assessed by estimating the glomerular filtration rate (GFR).Our retrospective analysis compared the assignment of 60 Caucasian volunteers to renal function groups based on their estimated GFR (eGFR). For each volunteer, GFR as measure of renal function was calculated using six commonly used equations (MDRD2006, CKD-EPIcreat2009, CKD-EPIcreat2021, CKD-EPIcyst2012, CKD-EPIcreat/cyst2012, and CKD-EPIcreat/cyst2021) with and without adjustment to individual body surface area (BSA).The resulting distribution of individuals to renal function groups varied across equations. The CKD-EPIcreat/cyst2012 and CKD-EPIcreat/cyst2021, using both creatinine and cystatin C, showed the highest consistency in the renal function group assignment (agreement rate). The agreement rate improved by adjusting with individual BSA (aGFR).The results support that BSA-adjustment of eGFR may improve the comparability and reproducibility of results of clinical trials where renal function categories are part of the trial design.